The Dynamics of The Transformation Policy of Ex-PNPM Into Bumdes Based on Government Regulation Number 11, 2021 - Dewi Dahlan; Ulya Fitri; Firdow Buerangae (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study explains the dynamics of the policy of transferring former PNPM into Village-Owned Enterprises (Bumdes). This transfer is based on Government Regulation No. 11 of 2021 concerning the Bumdes. This research was conducted in the former PNPM Sungai Tarab District. The purpose of this study is to examine how this transformation takes shape and what obstacles are faced by UPK DAPM Lenggogeni which is a former PNPM in transforming into a Joint Village Owned Enterprise (Bumdes). The research method used is descriptive qualitative research method. Interviews were conducted with the Chair of the DAPM Lenggogeni, Sungai Tarab Sub-district, the Secretary of Nagari, the Sub-district of Sungai Tarab and the Head of Community Empowerment of the Tanah Datar DPMD. The results obtained are that a number of former PNPM Financial Management Units (UPKs) are still skeptical of this change, this is because there are doubts about the transparency and accountability of PP No. 11 of 2021 which does not get clarity on the legal risks that are obtained if a UPK does not transform. The UPK also felt anxious and worried about the entry of intervention from outside parties so that it would cause conflict within the UPK.